Effect of Biochar Application Rate on Physical and Hydro-physical Properties of A Dystric Cambisol - Zachovalova, Marketa; Simeckova, Jana; Vlcek, Vitezslav; Hejduk, Stanislav; Jandak, Jiri (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2022)
The field trial evaluating the effect of biochar on physical and hydro-physical properties of a Dystric Cambisol was carried out at the Research Grassland Station Vatín. The observed variants of the biochar experiment were as follows: 1) the control without biochar, 2) the biochar rate of 15 t/ha applied to the topsoil, 3) the biochar rate of 30 t/ha applied to the topsoil and 4) the biochar rate of 45 t/ha applied to the topsoil. It was found out that even the highest rate of biochar 45 t/ha did not affect saturated hydraulic conductivity of the topsoil at the depth of 0.05-0.20 m. When monitoring bulk density, it was confirmed that the biochar rate of 45 t/ha significantly reduced bulk density from 1218 kg/m3 to 1169 kg/m3. In the crop rotation without manure and clover growing the application of biochar at the rate of 45 t/ha resulted in the relevant decline in the average value of bulk density from 1197 kg/m3 to 1138 kg/m3. In the Norfolk crop rotation there were the inconclusive differences in bulk density. The rate of 45 t/ha had a highly noticeable impact on porosity. It increased from 53.75% (0 t/ha) to 55.60%. The biochar doses did not affect the value of field capacity. The application of biochar at the rate of 45 t/ha caused the significant increase in the average value of aeration from 31.90% to 34.45%.